Pengaruh Konsentrasi Dan Variasi Waktu Inkubasi Terhadap Mutuvirgin Coconut Oil (VCO) - Fadhilah; Fadhilah azzah atiqah; Maria Yestiana M.K Leo; Siti Rahmah; Maria Imelda Humoen (Lembaga Teewan Journal Solutions, 2026)
This study aimed to evaluate the effect of baker’s yeast concentration and fermentation time on the quality of Virgin Coconut Oil (VCO) and to determine the optimal treatment for producing high-quality VCO. An experimental method was employed using a two-factor factorial Completely Randomized Design (CRD). The factors tested were yeast concentration (0 g, 1 g, and 2 g) and fermentation time (24, 36, and 48 hours). The observed parameters included yield, moisture content, free fatty acid (FFA) content, and organoleptic characteristics such as aroma, color, and taste. The results showed that both yeast concentration and fermentation time significantly affected (P < 0.05) VCO yield, moisture content, FFA levels, and organoleptic properties. The 1 g yeast treatment produced the best overall results, yielding 18.9% VCO with a moisture content of 0.21%, while the 2 g treatment did not show significant improvements in several parameters. The highest yield (19%) was obtained after 24 hours of fermentation, whereas 48 hours of fermentation resulted in a moisture content of 0.24% and an FFA value of 0.28%. Organoleptic evaluation indicated no significant differences in aroma and taste among treatments; however, fermentation time significantly influenced VCO color. Overall, the use of 1 g baker’s yeast combined with an appropriate fermentation period produced VCO with superior quality characteristics.